ANALYSIS OF ECONOMIC IMPACTS ABOUT TÜRKİYE-RUSSIA RELATIONS BEFORE AND AFTER PLANE CRISIS (Third Sector Social Economic Review, 2021)
Turkey and Russia have an extremely important position in terms of development and cooperation in the region as well as the ethnic and cultural ties and geographic locations historically. Increased trade volume and diplomatic dialogue between the two countries are the main reasons for the development of relations. In the post-Cold War era, Turkey and Russia have confronted each other for the first time due to aircraft crisis event as a primary issue.  After the crisis, Turkey has sent all the evidence to the hands the UN and NATO as part of the international laws. Russia has taken the decision to sanction Turkey by destroying the evolving strategic partnership between countries in the 2000s.In this study, the Turkish-Russian relations were analyzed from a historical perspective and shed light  on today's relations. This study aims to identify how and what extent the international trade has been changed in a political crisis with the fall of a Russian fighter aircraft by analyzing the past and present relations of Turkey and Russia. The latest statistical data from the sectors of energy, food, construction, tourism, etc. are included in the different sections of this study. The economic impact of the crisis to the relations between Turkey and Russia has been analysed.
Keywords: Russia; Turkey; Economic Crisis; Political Crisis